2017
DOI: 10.1111/coa.13018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of laryngectomy alone for treatment of locally advanced laryngeal cancer: A stage‐ and subsite‐specific survival analysis

Abstract: Locally advanced laryngeal cancer patients with T3 primaries, no nodal disease or primaries of the glottis may not benefit from post-operative radiotherapy when treated with primary total laryngectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“… 15 , 16 In addition, some epidemiological studies reported a decline in survival for patients with LSCC, possibly attributable to the increased use of RT and CRT protocols. 17 , 18 RT is considered an important adjunct for most of head and neck tumors, since it can address the residual microscopic tumor burden after the excision, but there are several factors related to the laryngeal anatomic disease that may reduce the likelihood of locoregional residual disease, 19 in particular, fascial barriers surrounding larynx that provide natural fence to tumor spread, the relatively poor lymphatic network from the glottis, and the wide margins achievable with interventions like total laryngectomy. 19 Differently from other head and neck tumor subsites, postoperative RT is not recommended for patients with T3 N0‐1 glottic cancer treated with total laryngectomy or T3 N0 glottic cancer treated with partial laryngectomy, in the absence of other high‐risk features (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 15 , 16 In addition, some epidemiological studies reported a decline in survival for patients with LSCC, possibly attributable to the increased use of RT and CRT protocols. 17 , 18 RT is considered an important adjunct for most of head and neck tumors, since it can address the residual microscopic tumor burden after the excision, but there are several factors related to the laryngeal anatomic disease that may reduce the likelihood of locoregional residual disease, 19 in particular, fascial barriers surrounding larynx that provide natural fence to tumor spread, the relatively poor lymphatic network from the glottis, and the wide margins achievable with interventions like total laryngectomy. 19 Differently from other head and neck tumor subsites, postoperative RT is not recommended for patients with T3 N0‐1 glottic cancer treated with total laryngectomy or T3 N0 glottic cancer treated with partial laryngectomy, in the absence of other high‐risk features (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…6 Despite these recommendation for selective use of postoperative RT in patients with locally advanced LSCC, many patients who underwent surgery are still treated with adjuvant RT. 19 Several authors have already questioned the role of postoperative RT for patient with T3 N0‐1 LSCC treated with primary surgery, 5 , 20 , 21 mainly because RT may deeply affect functional outcomes after laryngeal surgery, eventually decreased quality of life. 7 Moreover, the change in the laryngeal appearance might undermine follow‐up clinical examination and endoscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Compared with non-Medicaid insured groups, Medicaid insured cancer patients have been shown to have higher disease-specific mortality before diagnosis and higher mortality than the non-Medicaid groups after diagnosis. 10 Previous literature describes insurance status and type to be independent predictors of poor survival in laryngeal cancers, 11 and recent studies show disparities in nasopharyngeal carcinoma (NPC) survival among racial and ethnic minority groups in the United States. 12 To our knowledge, no study to date has specifically analyzed NPC survival outcomes with respect to insurance status.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients with advanced larynx cancer have locally advanced disease. 1 Advanced laryngeal cancer has a poor prognosis, and independent from the treatment method, 5-year survival rate is 39% to 60%. This is mostly because of being unable to control the regional and distant spread of the disease.…”
Section: Introductionmentioning
confidence: 99%